BUDAYA ETIKA, NIAT UNTUK BERTAHAN DALAM ORGANISASI DAN KESESUAIAN INDIVIDU DENGAN ORGANISASI SEBAGAI MEDIATOR (STUDI PADA PT. GARUDA INDONESIA MEDAN) - Mahdani Ibrahim; M. Haekal Mubarak (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2016)
This study examined the Effect of Ethical Culture to Person-Organization Fit and its impact on Intention to Stay (studied on PT. Garuda Indonesia Medan). The data collected is on the employees of PT. Garuda Indonesia Medan. A total of 84 respondents were included. Using Multiple Linear Regression Analysis, the results showed that: 1) Ethical Culture significant effect on Intention to Stay on employee PT. Garuda Indonesia Medan. 2) Person-Organization Fit significant effect on Intention to Stay on employee PT. Garuda Indonesia Medan. 3) Ethical Culture significant effect on Person-Organization Fit on employee PT. Garuda Indonesia Medan. 4) Ethical Culture significant effect on Intention to Stay mediated by Person-Organization Fit on employee PT. Garuda Indonesia Medan.